Mary Blair's unique flair : the girl who became one of the Disney legends - Novesky, Amy (Disney Press, 2019)
"Young Mary Browne Robinson loved color, even her name had a color in it. All she wanted to do was to make art. But becoming an artist wasn't an easy. Her parents worked hard to provide her paper and paints, and Mary worked hard to enter contests and earn a spot at a school for the arts. She even had to work hard to find her place at the Walt Disney Studios. But Walt was easily impressed by Mary Blair. When she joined his trip to South America, Mary had never seen such color. She collected that color and used it in her concept art for Cinderella, Alice in Wonderland, and Peter Pan, and even the It's a Small World attraction at Disneyland. This beautifully illustrated picture book shares Mary's story, in all its inspiring flair"--